(untitled) (CIPEEX, 2025)
Drunk driving is a critical public safety issue in Brazil, significantly contributing to fatal traffic accidents. This study analyzes the legal and social implications of drunk driving, focusing on the jurisprudential divergences regarding the characterization of *dolus eventualis* (eventual intent) and conscious negligence in accidents involving intoxicated drivers. Through qualitative and exploratory research, including a review of legislation such as the Brazilian Traffic Code and the Dry Law (Lei Seca), as well as jurisprudence and academic literature, this work examines the effectiveness of current legal frameworks. The results indicate that the lack of a judicial consensus on intent leads to inconsistent application of penalties, undermining their deterrent effect. Furthermore, the social and economic impacts of these accidents are severe, involving loss of life, high medical costs, and lost productivity. The conclusion emphasizes the urgent need for greater juridical uniformity in sanction application and reinforces the importance of integrated preventive strategies, such as educational campaigns, to foster a culture of responsibility and reduce traffic fatalities.